The foundation of studying the history of Islam and the Abbasid state in the perspective of modern and contemporary Western Orientalism - Aissaoui , Mohammed (Journal of Social Sciences and Humanities, 2021)
The research paper revolves around modern and contemporary Orientalism and its views on medieval history, and its contents addressed the essence of Orientalism, then the origins and motives of Orientalism, and then the foundations and approaches on which the oriental pioneers built their writings were addressed. The topic aims to develop a critical objective vision of Orientalist production, the historical method was used with its analytical and critical mechanisms. The research reached the importance of purposeful critical reviews, through which he filtered the features of the Orientalist historical research based on projecting Western perceptions on medieval history, generalizations in the issuance of judgments , the tendency to exaggerate doubt, assumption, and the adoption of what is not true of narrations, and in return there is an orientalist orientation neutral distanced himself from the approach of risk and prejudice.